EFL Students' Attitudes Towards Translanguaging Practice: Its Implications for Willingness to Communicate in Indonesian Vocational Classrooms - Kuncoroningtyas, Feby Sekar Ayu; Sumardi, Sumardi; Putra, Kristian Adi (Journal of Languages and Language Teaching, 2025)
Translanguaging has been recognized to help students learn a second language, yet many lecturers still see it as a problem rather than a useful educational tool. This study looks at the impact of translanguaging approaches on the confidence of Indonesian vocational college students in using English, with a focus mainly on the students' perspectives. The research used a qualitative case study to observe a class of 30 students (13 male and 17 female) in an English for Vocational Purposes (EVP) course. Four students, two females and two males were purposefully chosen for semi-structured interviews to get deeper perspectives. Data from these observations and interviews were evaluated thematically to better understand how translanguaging improves communication, strengthens teacher-student relationships, and assists in the processing of instructional materials. The findings indicate that students hold a positive attitude toward translanguaging pedagogies, citing benefits such as improved knowledge development, enhanced vocabulary acquisition, stronger relationships with lecturers, and increased Willingness to Communicate (WTC) in English. The study emphasizes that translanguaging facilitates English language learning and acknowledges and embraces the linguistic diversity of Indonesian classrooms. This research provides important information for policymakers, educators, and researchers on how utilizing translanguaging in EFL teaching approaches can be essential in creating a more inclusive and effective learning atmosphere, especially in diverse educational settings.